The Status and Role of Chinese Women in the Short Stories Complied Book Entitled “Siang Phriak Thee Klob Ren Jak Pan Din Yai” - Leshan, Peng; พลมณี, ศรีวิไล; สัตโยภาส, สนิท (Ganesha Journal, 2019)
This research aimed to analyze the status and role of chinese women in complied books entitled "Siang Phreak Thee Klob Ren Jak Pan Din Yai " by analyzing the status and role of Chinese women, from the main characters who played important role in the handling of 6 issues of 15 issues. The study was found as followed: Status from birth and family status; chinese women had family status as follows. 1.1 The status of daughter, they had the role in respecting obedience to parental commands , parental reward and helping to work within the family. 1.2 The status of wives, they had the role in caring, honoring, respecting and obeying the husband, accepting the role of husband as head of family and role of pregnancy. 1.3 The status of mother, they had the role of caring for children and encourage their child to succeed in life. 1.4 The status of women of the family, they had been used by men to support sexual needs of men in the family and to have children . Social status 2.1 Social status before the reform and opening up of the country, chinese women had no social status due to the old beliefs and the old traditions and the importance of men. Chinese men could work outside but women had no handle housework at home. 2.2 Social status after the reform and opening of the country. Young Chinese were encouraged to study and get higher education because they would have important role in country development. These opportunities allowed Chinese women to participate in reformation. They could also succeed in working like men did.